KEANEKARAGAMAN JENIS BURUNG DI HUTAN LARANGAN ADAT KENEGERIAN RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR PROVINSI RIAU - Sabaruddin Sabaruddin; Defri Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Bird is one of the biodiversity must be preserved from extinction and decline in species diversity. Forest Reserve of Kenegerian Rumbio have potential as bird species diversity. Species of birds in the forest has not data and information about the birds. This study aims to determine the level of bird species diversity and relative abundance of birds in the forest Reserve of Kenegerian Rumbio.Diversity of bird species in the Forest Reserve of Kenegerian Rumbio found 40 species of birds from 21 families. Index of bird species diversity in each region indicates that is Panogan (H '= 2.57), Sialang Layang (H' = 2.7), Halaman Kuyang (H '= 2.37) and Tanjung Kulim (H' = 2.55). Value Relative Abundance (VRA) species of birds in each different region. Relative Abundance Index (RAI)Panogan zone 18.97%, 20.22% Sialang Layang,Halaman Kuyang 22% and 20.83% of Tanjung Kulim and included in the high category.Keyword: Biodiversity, Bird, Forest Reserve of Kenegerian Rumbio